2001
DOI: 10.1515/jpem.2001.14.9.1597
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Screening for Congenital Hypothyroidism, Victoria, Australia, 1977-1997. Part 1: The Screening Programme, Demography, Baseline Perinatal Data and Diagnostic Classification

Abstract: Clinical, demographic and laboratory data from infants with congenital hypothyroidism (CH) born in the Australian state of Victoria from the commencement of neonatal screening in mid-1977 until December 1988 are reported. These provide a baseline for a 12-year prospective longitudinal study on physical and neuro-psychological outcome until mid-1997, the subject of a second paper. Infants with CH were detected using a primary TT4 screening test. Demographic data were collected prospectively using a clinical ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
2
13
0
1
Order By: Relevance
“…Due to the retrospective nature of our study, we were unable to accurately determine the proportion of children in our study who had familial forms of thyroid dysgenesis. Based on the reported frequency of approximately 2% of familial thyroid dysgenesis (16,24), we would only expect 2 patients in our series of 117 patients with ectopia and athyreosis to have a familial basis, thus making any form of statistical analysis of the familial cases impossible even if we were able to identify them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the retrospective nature of our study, we were unable to accurately determine the proportion of children in our study who had familial forms of thyroid dysgenesis. Based on the reported frequency of approximately 2% of familial thyroid dysgenesis (16,24), we would only expect 2 patients in our series of 117 patients with ectopia and athyreosis to have a familial basis, thus making any form of statistical analysis of the familial cases impossible even if we were able to identify them.…”
Section: Discussionmentioning
confidence: 99%
“…Many questions remain regarding the molecular contributions to the dimorphic physiologies of males and females. It has been suggested that only 2% of patients with thyroid dysgenesis incorporating the spectrum of ectopia and athyreosis have a familial basis (16,24). The female preponderance was observed in sporadic forms of thyroid dysgenesis with almost thrice the number of girls affected (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…As per the standard newborn screening procedure (1,2 ), the neonatal screening test was repeated on day 17, and although lower than the previous measurement, the TSH was again above the URL (TSH, 19.6 mIU/L; URL, 10.0 mIU/L). On day 21 of life, the child was euthyroid, had thrived since birth with a current weight of 3600 g, and was feeding well.…”
Section: Factitious Increase In Thyrotropin In a Neonate Caused By A mentioning
confidence: 99%
“…An Australian study has reported that 62% of infants diagnosed with CH have jaundice, 54% have an umbilical hernia, 41% have edema, and 21% have a protruding tongue, whereas only 6% show an enlarged thyroid on palpation. 48 In addition, approximately 15% of CH children also show an increased incidence of major congenital malformations, 48 particularly cardiac (7%) and urogenital (3%) abnormalities.…”
Section: Congenital Hypothyroidismmentioning
confidence: 99%